2019
DOI: 10.1177/0144598719871628
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wind power potential by the three-parameter Weibull distribution to install a wind turbine

Abstract: Energy is essential for any country’s economic growth and is inevitable in improving the standard of life of its citizens. Since independence, India has spent considerable resources on increasing its energy capacity. As a result, the country’s energy generation capacity has increased considerably. Wind energy is a clean and eco-friendly energy source and is increasingly being accepted as a major complementary energy source for securing a sustainable and clean energy for future in India. The appropriate wind sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…For each time series obtained, the frequency distribution of the wind intensity and the probability density function (PDF), f ( v ), 33,35,36 are calculated using the following equation: f()v=kcvck1e[]vck where v is the wind speed in m/s and the parameters k > 0 and c > 1 are the scale factor and the shape factor, respectively 37 …”
Section: Methodsmentioning
confidence: 99%
“…For each time series obtained, the frequency distribution of the wind intensity and the probability density function (PDF), f ( v ), 33,35,36 are calculated using the following equation: f()v=kcvck1e[]vck where v is the wind speed in m/s and the parameters k > 0 and c > 1 are the scale factor and the shape factor, respectively 37 …”
Section: Methodsmentioning
confidence: 99%
“…The parameters k and c depend on the location of the wind source. Several methodologies using the available wind speed data such as least-squares fit methods, maximum likelihood method, and method of moments [56] have been proposed to estimate k and c. Moreover, many computer modelling packages, such as HOMER and WASP, have been used in several works for estimating these parameters [57]. In [1], it is suggested that [1.0-3.0] and [5.0-20.0] are suitable ranges for the shape and scale factors, respectively.…”
Section: Equivalent Deterministic Model For the Eed Problem Includingmentioning
confidence: 99%
“…Therefore, its usage cannot be generalized. To minimize errors, a suitable probability density function must be carefully selected for different wind regimes (Carta et al 2009;Sukkiramathi and Seshaiah, 2020). Tuller and Brett (1984) proposed a three-parameter Weibull function in wind analysis and found that it showed better fitness and flexibility than the two-parameter Weibull function.…”
Section: Introductionmentioning
confidence: 99%
“…The author compared the wind speeds for three different sites and found that the threeparameter Weibull distribution performed best when there was a greater frequency of lower wind speeds. Sukkiramathi and Seshaiah (2020) also utilized the three-parameter Weibull distribution for analyzing wind power potential. However, to date, only limited research has been carried out on wind analysis using the three-parameter Weibull distribution.…”
Section: Introductionmentioning
confidence: 99%